A method for preparing high-density aluminum nitride ceramics
Patent Information
- Application Number
- CN202611258828.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-16
AI Technical Summary
本发明目的在于提供一种高密度氮化铝陶瓷制备方法,解决现有流延法排胶过程中,因坯体内部缺乏连通排气通道,有机粘结剂集中产气无法及时逸出所导致的坯体开裂问题
[0014]In summary, due to the adoption of the above technical solutions, the beneficial effects of this invention are as follows: By introducing a hydrolyzable pore-forming agent into the slurry and setting a humidity pretreatment step and a two-stage constant-temperature debinding system, the three work synergistically in the process sequence to construct an exhaust channel inside the green body before the binder decomposes in large quantities, providing an escape path for the decomposition gases of the binder and reducing the risk of debinding cracking; before the humidity pretreatment step, the AlN powder undergoes phosphate ester surface passivation treatment, reducing the degree of AlN hydrolysis during the humidity pretreatment process, so that the increase in the oxygen content of the green body is controlled within a predetermined range while the pore-forming agent hydrolyzes; the hydrolyzable pore-forming agent contains only carbon, hydrogen, and oxygen, and its decomposition products escape in gaseous form at the debinding temperature, without introducing impurities such as metals, silicon, and halogens; the humidity pretreatment step introduces moisture as a process control measure into the green body treatment process before debinding, providing a process path different from the traditional water-avoidance approach for improving the degassing capacity of the green body. In addition, the pore-forming agent is directly dissolved in the organic solvent of the slurry, requiring no additional dispersion process, and has high compatibility with existing casting and debinding equipment, making it easy to implement on existing production lines.
Smart Images

Figure CN122916685A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aluminum nitride ceramic production technology, specifically a method for preparing high-density aluminum nitride ceramics. Background Technology
[0002] Aluminum nitride ceramics possess high thermal conductivity and excellent electrical insulation properties, making them a key material for substrates of high-power electronic devices. Their large-scale production primarily employs the casting method. During the binder removal process, the organic binder within the green body decomposes at high temperatures, generating a large amount of gas. However, the dense structure of the green body lacks interconnected venting channels, resulting in high resistance to gas escape and internal pressure buildup that easily leads to cracking. Industrially, an extremely slow heating rate is commonly used to alleviate this problem. This method reduces internal pressure by slowing down the gas generation rate, but the lack of interconnected venting channels within the green body remains unchanged, and the risk of cracking during binder removal persists. Attempts have also been made to add sinterable pore-forming agents, but the decomposition temperature of these agents overlaps with the binder's decomposition window, making it impossible to pre-build an independent venting network before gas generation.
[0003] The underlying reason for the above predicament is that the industry has long regarded the desorption process as a purely thermal decomposition process, and its solutions are limited to passive adaptation, rather than re-examining the issue from the perspective of actively building exhaust channels. At the same time, due to the easy hydrolysis of aluminum nitride, moisture is strictly regarded as a harmful factor, which has led to the long-term neglect of the technical path of using humidity to trigger chemical reactions to build exhaust channels. Summary of the Invention
[0004] (1) Technical problems to be solved The purpose of this invention is to provide a method for preparing high-density aluminum nitride ceramics, which solves the problem of cracking of the green body caused by the lack of a connected exhaust channel inside the green body during the existing tape casting process, resulting in the inability of the concentrated gas generated by the organic binder to escape in time.
[0005] (2) Technical solution To achieve the above objectives, this invention provides a method for preparing high-density aluminum nitride ceramics, comprising the steps of preparing aluminum nitride powder, slurry preparation, tape casting, binder removal, and sintering. The aluminum nitride powder is passivated with phosphate ester before the slurry is prepared. A hydrolyzable pore-forming agent is added in the slurry preparation step. The hydrolyzable pore-forming agent is prepared by reacting ethylene glycol, diethyl carbonate and triethyl orthoformate. A humidity pretreatment step is added after the casting step and before the glue removal step to treat the humidity of the dried blank. The glue removal step includes a first constant temperature platform and a second constant temperature platform.
[0006] Furthermore, the preparation method of the hydrolyzable porogen includes the following steps: Ethylene glycol and diethyl carbonate were reacted in the presence of a catalyst, and ethanol was distilled off. Triethyl orthoformate was added, and the reaction continued. The ester was removed under vacuum to obtain the hydrolyzed porogen.
[0007] Furthermore, the catalyst is tetrabutyl titanate, and the amount added is 0.05% to 0.5% of the total mass of ethylene glycol, diethyl carbonate and triethyl orthoformate; the molar ratio of added diethyl carbonate to triethyl orthoformate is 1 to 3:1.
[0008] Furthermore, the amount of the hydrolyzable pore-forming agent added accounts for 12-22% of the total mass of the organic components in the slurry.
[0009] Furthermore, the temperature of the humidity pretreatment step is 30-45°C, the relative humidity is 40-80%, the time is 1-4 hours, and the atmosphere is nitrogen carrying water vapor.
[0010] Furthermore, during the humidity pretreatment process, the NH3 concentration in the exhaust gas is monitored to control the degree of hydrolysis side reaction of the AlN matrix. When the NH3 concentration exceeds the preset threshold, it indicates that AlN hydrolysis is intensified, and the humidity needs to be reduced or the treatment time shortened to control the increase in oxygen content of the green body.
[0011] Furthermore, in the glue removal step, the temperature of the first constant temperature platform is 120-150℃, and the holding time is 0.5-2h; the temperature of the second constant temperature platform is 180-250℃, and the holding time is 0.5-1.5h.
[0012] Furthermore, after the first and second constant temperature platforms, the temperature is further increased to 350-450°C to complete the decomposition of the main adhesive, and finally the temperature is increased to 550-650°C to complete the removal of adhesive.
[0013] Furthermore, after the humidity pretreatment, the increase in oxygen content of the billet measured by the inert gas melting method is controlled to be below 0.5 wt%.
[0014] In summary, due to the adoption of the above technical solutions, the beneficial effects of this invention are as follows: By introducing a hydrolyzable pore-forming agent into the slurry and setting a humidity pretreatment step and a two-stage constant-temperature debinding system, the three work synergistically in the process sequence to construct an exhaust channel inside the green body before the binder decomposes in large quantities, providing an escape path for the decomposition gases of the binder and reducing the risk of debinding cracking; before the humidity pretreatment step, the AlN powder undergoes phosphate ester surface passivation treatment, reducing the degree of AlN hydrolysis during the humidity pretreatment process, so that the increase in the oxygen content of the green body is controlled within a predetermined range while the pore-forming agent hydrolyzes; the hydrolyzable pore-forming agent contains only carbon, hydrogen, and oxygen, and its decomposition products escape in gaseous form at the debinding temperature, without introducing impurities such as metals, silicon, and halogens; the humidity pretreatment step introduces moisture as a process control measure into the green body treatment process before debinding, providing a process path different from the traditional water-avoidance approach for improving the degassing capacity of the green body. In addition, the pore-forming agent is directly dissolved in the organic solvent of the slurry, requiring no additional dispersion process, and has high compatibility with existing casting and debinding equipment, making it easy to implement on existing production lines. Attached Figure Description
[0015] Figure 1 This is a flowchart of the high-density aluminum nitride ceramic preparation method of the present invention.
[0016] Figure 2 This is a SEM image of the aluminum nitride powder of the present invention. Detailed Implementation
[0017] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0018] Example 1: A method for preparing high-density aluminum nitride ceramics, comprising the steps of preparing aluminum nitride powder, slurry preparation, tape casting, binder removal, and sintering. A hydrolyzable pore-forming agent is added in the slurry preparation step. The hydrolyzable pore-forming agent is prepared by reacting ethylene glycol, diethyl carbonate and triethyl orthoformate. A humidity pretreatment step is added after the casting step and before the glue removal step to treat the humidity of the dried blank. The glue removal step includes a first constant temperature platform and a second constant temperature platform.
[0019] The preparation method of the hydrolyzable porogen includes the following steps: Weigh out 68.2 g of ethylene glycol, 130.1 g of diethyl carbonate, 81.5 g of triethyl orthoformate, and 0.28 g of tetrabutyl titanate. Add ethylene glycol and diethyl carbonate to a reaction vessel, heat to 130 °C under nitrogen protection, add tetrabutyl titanate, stir and react for 2 h, and distill off the generated ethanol. Then cool to 90 °C, add triethyl orthoformate, and continue stirring and reacting for 1.5 h. After the reaction is complete, evacuate to -0.09 MPa to remove residual ethanol and small molecule byproducts, cool to obtain a hydrolyzable porogen, and seal for storage.
[0020] like Figure 1 As shown, the method for preparing high-density aluminum nitride ceramics includes the following steps: S1: Weigh 900g of boehmite and 400g of sucrose, mix and grind them evenly, stir at 100℃ and spray dry to obtain the precursor; nitrid the precursor at 1650℃ for 4h in a nitrogen atmosphere, then cool to 600℃ and remove carbon in an oxygen-containing atmosphere for 2h to obtain aluminum nitride powder; its SEM image is shown below. Figure 2 As shown; 1.5g of phosphate ester was dissolved in 100mL of anhydrous ethanol, and 100g of the above aluminum nitride powder was added. After stirring and dispersing evenly, the mixture was vacuum dried at 60℃ for 2h to obtain aluminum nitride powder with phosphate ester passivation treatment on the surface. S2: Take 100g of aluminum nitride powder after S1 passivation treatment, add it to a mixed solvent composed of 70g butyl acetate and 30g anhydrous ethanol, then add 1.5g phosphate dispersant and 4g dibutyl phthalate plasticizer, and ball mill and mix for 4h; then add 8g polyvinyl butyral, and continue ball milling for 2h until completely dissolved; finally add 2.76g of the above-mentioned pore-forming agent, stir at low speed for 30min, and obtain the casting slurry; in this embodiment, the organic components of the slurry include 1.5g dispersant, 4g plasticizer, 8g PVB, and 2.76g pore-forming agent, with a total organic component mass of 16.26g, and the amount of pore-forming agent added accounts for 17.0% of the total organic component mass; S3: After vacuum degassing the slurry obtained in S2, it is formed by tape casting and then gradually dried at 65~70℃ to obtain a tape casting preform; S4: The cast green body obtained in S3 is placed in a nitrogen-carrying water vapor atmosphere at 38°C and 60% relative humidity and left to stand for 2.5 hours. The NH3 concentration in the exhaust gas is monitored during the pretreatment process and does not exceed the preset threshold. In this embodiment, the initial oxygen content of the green body after passivation without humidity treatment is 0.48 wt%; after the humidity pretreatment in S4, the total oxygen content of the green body is 0.83 wt%; the oxygen content increase is 0.35 wt%. S5: Transfer the preform treated in S4 into the debinding furnace and perform step debinding in a nitrogen atmosphere; raise the temperature from room temperature to 135℃ at 1℃ / min and hold for 1.25h; then raise the temperature to 215℃ at 0.5℃ / min and hold for 1h; then raise the temperature to 400℃ at 0.5℃ / min and hold for 1.5h; finally raise the temperature to 600℃ at 1℃ / min and hold for 1h to complete the debinding. S6: Place the blank after debinding in S5 into a high-temperature sintering furnace under a nitrogen atmosphere. Use yttrium oxide as a sintering aid, with an addition amount of 4% of the mass of aluminum nitride powder in step S1. Heat the blank to 1850°C at 3°C / min and hold for 35 hours for pressureless sintering. After cooling in the furnace, a high-density aluminum nitride ceramic substrate is obtained.
[0021] The catalyst is tetrabutyl titanate, and the amount added is 0.1% of the total mass of ethylene glycol, diethyl carbonate and triethyl orthoformate; the molar ratio of added diethyl carbonate to triethyl orthoformate is 2:1.
[0022] The amount of the hydrolyzable porogen added accounts for 17% of the total mass of the organic components in the slurry.
[0023] The humidity pretreatment step is performed at a temperature of 38°C, a relative humidity of 60%, for a time of 2.5 hours, and in an atmosphere of nitrogen carrying water vapor.
[0024] In the glue removal step, the temperature of the first constant temperature platform is 135℃ and the holding time is 1.25h; the temperature of the second constant temperature platform is 215℃ and the holding time is 1h.
[0025] After the first and second constant temperature platforms, the temperature is further increased to 400°C to complete the decomposition of the main adhesive, and finally the temperature is increased to 600°C to complete the removal of adhesive.
[0026] Example 2: Compared with Example 1, the difference is that 1.84g of hydrolyzable porogen was added in S2, the total mass of organic components was 15.34g, and the amount of hydrolyzable porogen added accounted for 12.0% of the total mass of organic components; the humidity pretreatment temperature in S4 was 30℃, the relative humidity was 40%, and the time was 1h, the initial oxygen content after passivation was 0.47wt%, the final oxygen content was 0.73wt%, and the oxygen content increase was 0.26wt%; the temperature of the first isothermal platform in S5 was 120℃ and the holding time was 0.5h, and the temperature of the second isothermal platform was 180℃ and the holding time was 0.5h; the sintering temperature in S6 was 1800℃ and the holding time was 30h; the remaining steps were the same as in Example 1.
[0027] Example 3: Compared with Example 1, the difference is that 3.81g of hydrolyzable porogen was added in S2, the total mass of organic components was 17.31g, and the amount of hydrolyzable porogen added accounted for 22.0% of the total mass of organic components; the humidity pretreatment temperature in S4 was 45℃, the relative humidity was 80%, and the time was 4h, the initial oxygen content after passivation was 0.48wt%, the final oxygen content was 0.90wt%, and the oxygen content increase was 0.42wt%; the temperature of the first isothermal platform in S5 was 150℃ and the holding time was 2h, and the temperature of the second isothermal platform was 250℃ and the holding time was 1.5h; the sintering temperature in S6 was 1900℃ and the holding time was 40h; the remaining steps were the same as in Example 1.
[0028] Comparative Example 1: Compared with Example 1, the difference is that no hydrolyzable pore-forming agent is added in the preparation of the slurry in S2; the humidity pretreatment step in S4 is omitted and the glue is directly discharged; the glue discharge step in S5 adopts the same heating regime as in Example 1; the remaining steps are the same as in Example 1.
[0029] Comparative Example 2: Compared with Example 1, the difference is that the S4 humidity pretreatment step is omitted, and the S3 cast blank directly enters the S5 glue removal step after drying; the remaining steps are the same as in Example 1.
[0030] Comparative Example 3: Compared with Example 1, the difference is that the first and second constant temperature platforms are not set in the S5 glue removal step. Instead, the temperature is raised from room temperature to 600°C at a constant rate of 1°C / min and kept at that temperature for 1 hour. The remaining steps are the same as in Example 1.
[0031] Comparative Example 4: Compared with Example 1, the difference is that 6g of hydrolyzable porogen was added in the preparation of S2 slurry, the total mass of organic components was 19.5g, and the amount of hydrolyzable porogen added accounted for 30.8% of the total mass of organic components; the remaining steps were the same as in Example 1.
[0032] Comparative Example 5: Compared with Example 1, the difference is that the hydrolytic porogen is replaced with polyethylene carbonate (containing only carbonate bonds and no orthoester bonds), and the preparation method is to obtain it by polycondensation of ethylene glycol and diethyl carbonate in a molar ratio of 1:1.1 in the presence of a catalyst; the remaining steps are the same as in Example 1.
[0033] Comparative Example 6: Compared with Example 1, the difference is that the hydrolytic porogen is replaced with polyethylene orthoformate (containing only orthoester bonds and no carbonate bonds), and the preparation method is to obtain it by polycondensation of ethylene glycol and triethyl orthoformate in the presence of a catalyst; the remaining steps are the same as in Example 1.
[0034] Comparative Example 7: Compared with Example 1, the difference is that the AlN powder was not passivated with phosphate ester. The remaining steps are the same as in Example 1; due to the lack of passivation of the AlN powder, the degree of AlN hydrolysis increased significantly under the same humidity pretreatment conditions; the initial oxygen content of the pretreated green body was 0.48 wt%, the final oxygen content was 0.96 wt%, and the oxygen content increment was 0.48 wt%, significantly higher than the 0.35 wt% in Example 1. The thermal conductivity of the substrate after sintering was 172 W / (m·K).
[0035] Comparative Example 8: Compared with Example 1, the difference is that in the preparation of S2 slurry, the hydrolyzable pore-forming agent is added to the ball mill jar together with aluminum nitride powder, solvent, dispersant and plasticizer before ball milling and mixing. After ball milling and mixing for 4 hours, the main binder is added and ball milling continues for 2 hours; the remaining steps are the same as in Example 1.
[0036] Comparative Example 9: Compared with Example 1, the difference is that the hydrolyzable pore-forming agent is replaced with polymethyl methacrylate (PMMA) microspheres, a commonly used burnable pore-forming agent in the prior art, and the amount added accounts for 17.0% of the total mass of organic components in the slurry; the remaining steps are the same as in Example 1.
[0037] Comparative Example 10: Compared with Example 1, the difference is that no hydrolyzable pore-forming agent is added in the preparation of the slurry in S2; the humidity pretreatment step in S4 is omitted and the glue is directly removed; in the glue removal step in S5, the heating rate in the range of 350-450℃ is adjusted from 0.5℃ / min to 0.2℃ / min, and the holding time at 400℃ is extended from 1.5h to 3h; the remaining steps are the same as in Example 1.
[0038] Experimental verification: Experiment 1: Comparison of glue removal yield; Take 20 cast iron blanks prepared in each of Examples 1-3, Comparative Examples 1-3, and Comparative Examples 5-10. Place the seven groups of blanks into the debinding furnace and debind them according to their respective debinding procedures. After debinding, cool them to room temperature in the furnace and take them out to inspect them under natural light and with the help of a magnifying glass to check whether there are defects such as cracks, bulges, or delamination on the surface and edges of each blank. Any macroscopic defect is considered as cracking. Count the number of blanks without cracks in each group and calculate the debinding yield. The test results are shown in Table 1.
[0039] Table 1 Comparison of glue removal yield:
[0040] The experimental results show that the debinding yield of Example 1 is better than that of the comparative examples, while the debinding yields of Examples 2 and 3 are similar to those of Example 1. Comparative Example 1, which did not introduce a porogen, has a lower debinding yield. Comparative Example 2, which did not undergo humidity pretreatment, and Comparative Example 3, which did not have a two-stage constant temperature platform, both have lower debinding yields than Example 1. Comparative Examples 5 and 6 have incomplete porogen bond structures, resulting in lower debinding yields than Example 1. The debinding yield of Comparative Example 7 is similar to that of Example 1, indicating that phosphate ester passivation treatment mainly affects oxygen content and thermal conductivity, and has no significant impact on debinding yield. Comparative Example 8, where the porogen was added in advance... The yield of Comparative Example 9 was lower than that of Example 1, indicating that the process order of adding the pore-forming agent after the binder is of practical significance in ensuring its function. Comparative Example 9 used existing PMMA microspheres, and the yield was significantly lower than that of Example 1, indicating that existing burnable pore-forming agents cannot pre-build venting channels. Comparative Example 10 used an industrially slow heating rate but no pore-forming agent. Although the yield was improved compared to Comparative Example 1, it was still lower than that of Example 1, and the debinding cycle was greatly extended, indicating that simply slow heating did not change the nature of insufficient channels. The above results show that the process condition combination of Example 1 is better than other comparative schemes in terms of debinding yield.
[0041] Experiment 2: Comparative Test of Substrate Physical Properties; Take intact blanks that did not crack after debinding from Examples 1-3 and Comparative Examples 2, 3, 5-10, with no less than 3 pieces in each group; Comparative Example 1 was not included in this test because it was severely cracked after debinding and the number of intact blanks was insufficient. Place each group of blanks in a high-temperature sintering furnace under nitrogen atmosphere, and the sintering conditions of each group of blanks are exactly the same; use yttrium oxide as a sintering aid, with an addition amount of 4% of the mass of aluminum nitride powder, heat to 1850℃ at 3℃ / min, hold for 35h under nitrogen atmosphere, and cool with the furnace.
[0042] Bulk density test: The sintered substrate sample was boiled in deionized water for 2 hours to allow water to fully penetrate and open the pores. After removal, the dry weight of the sample in air, the wet weight of the saturated sample in air, and the buoyant weight of the saturated sample in water were measured. The bulk density was calculated using the following formula: ; In the formula: ρ — bulk density of the sample, g / cm³ 3 ; m1—mass of the dried sample in air, g; m2—mass of the saturated sample in air, in grams; m3 — the mass of the saturated sample in water, in grams; ρ0 — Density of deionized water at the test temperature, g / cm³ 3 .
[0043] Thermal conductivity testing: The sintered substrate sample was processed into a circular wafer with a diameter of 12.7 mm and a thickness of 2–3 mm. Graphite coatings were sprayed onto both the upper and lower surfaces. At 25°C, a pulsed laser was emitted from a laser flare instrument to irradiate the lower surface of the sample, and an infrared detector recorded the temperature rise curve of the upper surface to obtain the thermal diffusivity. Thermal conductivity was calculated using the following formula: ; In the formula: λ—thermal conductivity, W / (m·K); α — Thermal diffusivity, mm 2 / s; C p —Specific heat capacity, J / (g·K); ρ—bulk density, g / cm³ 3 .
[0044] Table 2 Comparison of physical properties:
[0045] The experimental results show that the substrate performance of Examples 2 and 3 is similar to that of Example 1; Comparative Example 2 did not undergo humidity pretreatment, and Comparative Example 3 did not have a two-stage constant temperature platform, resulting in substrate performance lower than that of Example 1; Comparative Examples 5 and 6 had incomplete pore-forming agent bond types, leading to substrate performance lower than that of Example 1; the AlN powder in Comparative Example 7 was not subjected to phosphate passivation treatment, resulting in significantly lower thermal conductivity than that of Example 1, indicating that phosphate passivation treatment plays a crucial role in inhibiting AlN hydrolysis and ensuring the thermal conductivity of the substrate; Comparative Example 8 changed the order of pore-forming agent addition, and the substrate performance was also lower than that of Examples 1. Example 1; Comparative Example 9 used existing PMMA microspheres as a pore-forming agent, and its bulk density and thermal conductivity were lower than those of Example 1, indicating that existing burnable pore-forming agents cannot pre-build independent exhaust channels, thus affecting sintering densification and thermal conductivity. Comparative Example 10 used an industrially extremely slow heating rate but did not add a pore-forming agent, and the substrate performance was still lower than that of Example 1, indicating that simply relying on an extremely slow heating rate cannot achieve the substrate densification and thermal conductivity that can be obtained by the present invention. The above results show that the combination of process conditions in Example 1 can obtain a better substrate densification and thermal conductivity.
[0046] Experiment 3: Verification of the effect of pore-forming agent addition amount on the structure of the preform; Following the method of Example 1, only the amount of pore-forming agent added was changed, so that its proportion of the total mass of organic components in the slurry was 6%, 12%, 17%, 24%, and 30.8%, respectively, and 10 cast blanks were prepared for each group; the 17% addition group was Example 1, and the 30.8% addition group was Comparative Example 4; the blanks in each group were subjected to humidity pretreatment and debinding according to the conditions of Example 1; after debinding, the cracking and deformation of the blanks were checked; the intact blanks were selected and sintered according to the conditions of Example 1, and the bulk density and thermal conductivity of the substrate were tested.
[0047] Table 3 Comparison of preform state under different pore-forming agent addition amounts:
[0048] Table 4 Comparison of physical properties of substrates with different amounts of porogen:
[0049] The experimental results show that when the amount of pore-forming agent added is low, the preform exhibits more cracks; as the amount added increases, cracking and deformation are effectively controlled, and the substrate performance is improved; at the amount of pore-forming agent added in Example 1, the preform is intact and the substrate performance is optimal; when the amount added is too high, the preform deforms and the substrate performance decreases significantly; when the amount added reaches 30.8% (Comparative Example 4), the preform deforms significantly and the substrate performance decreases substantially; the above results indicate that the amount of pore-forming agent added within the range defined in the claims can balance the glue removal yield and substrate performance, and the amount added in Example 1 is within a suitable range.
[0050] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, and improvements made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing high-density aluminum nitride ceramic, characterized in that, This includes the steps of preparing aluminum nitride powder, slurry preparation, casting, debinding, and sintering. The aluminum nitride powder is passivated with phosphate ester before the slurry is prepared. A hydrolyzable pore-forming agent is added in the slurry preparation step. The hydrolyzable pore-forming agent is prepared by reacting ethylene glycol, diethyl carbonate and triethyl orthoformate. A humidity pretreatment step is added after the casting step and before the glue removal step to treat the humidity of the dried blank. The glue removal step includes a first constant temperature platform and a second constant temperature platform.
2. The method for preparing high-density aluminum nitride ceramic according to claim 1, characterized in that, The preparation method of the hydrolyzable porogen includes the following steps: Ethylene glycol and diethyl carbonate were reacted in the presence of an ester exchange catalyst, ethanol was distilled off, triethyl orthoformate was added, the reaction was continued, and the ester was removed under vacuum to obtain the hydrolyzed porogen.
3. The method according to claim 2, characterized in that, The catalyst is tetrabutyl titanate, and the amount added is 0.05% to 0.5% of the total mass of ethylene glycol, diethyl carbonate and triethyl orthoformate; the molar ratio of added diethyl carbonate to triethyl orthoformate is 1 to 3:
1.
4. The method for preparing high-density aluminum nitride ceramic according to claim 1, characterized in that, The amount of the hydrolyzable porogen added accounts for 12-22% of the total mass of the organic components in the slurry.
5. The method for preparing high-density aluminum nitride ceramic according to claim 1, characterized in that, The humidity pretreatment step is performed at a temperature of 30–45°C, a relative humidity of 40–80%, for a time of 1–4 hours, and in an atmosphere of nitrogen carrying water vapor.
6. A method for preparing high-density aluminum nitride ceramic according to claim 1 or 5, characterized in that, During the humidity pretreatment process, the NH3 concentration in the exhaust gas is monitored to control the degree of hydrolysis side reaction of the AlN matrix. When the NH3 concentration exceeds the preset threshold, it indicates that AlN hydrolysis is intensified, and the humidity needs to be reduced or the treatment time shortened to control the increase in oxygen content of the green body.
7. The method for preparing high-density aluminum nitride ceramic according to claim 1, characterized in that, In the glue removal step, the temperature of the first constant temperature platform is 120-150℃, and the holding time is 0.5-2h; the temperature of the second constant temperature platform is 180-250℃, and the holding time is 0.5-1.5h.
8. A method for preparing high-density aluminum nitride ceramic according to claim 1 or 7, characterized in that, After the first and second constant temperature platforms, the temperature is further increased to 350-450℃ to complete the decomposition of the main adhesive, and finally the temperature is increased to 550-650℃ to complete the removal of adhesive.
9. The method for preparing high-density aluminum nitride ceramic according to claim 1, characterized in that, After the humidity pretreatment, the increase in oxygen content of the green body, measured by the inert gas melting method, is controlled to be below 0.5 wt%.